Unique Neural Characteristics of Atypical Lateralization of Language in Healthy Individuals - Biduła, Szymon P.; Przybylski, Łukasz; Pawlak, Mikołaj A.; Króliczak, Gregory (Frontiers in Neuroscience, 2017)
Using functional magnetic resonance imaging (fMRI) in 63 healthy participants, including left-handed and ambidextrous individuals, we tested how atypical lateralization of language – i.e., bilateral or right hemispheric language representation – differs from the typical left-hemisphere dominance. Although regardless of their handedness, all 11 participants from the atypical group engaged classical language centers, i.e., Broca’s and Wernicke’s areas, the right-hemisphere components of the default mode network, including the angular gyrus and middle temporal gyrus, were also critically involved during the verbal fluency task. Importantly, activity in these regions could not be explained in terms of mirroring the typical language pattern because left-hemisphere dominant individuals did not exhibit similar significant signal modulations. Moreover, when spatial extent of language-related activity across whole brain was considered, the bilateral language organization entailed more diffuse functional processing. Finally, we detected significant differences between the typical and atypical group in the resting-state connectivity at the global and local level. These findings suggest that the atypical lateralization of language has unique features, and is not a simple mirror image of the typical left hemispheric language representation.